APPLICANT LEGAL STANDING BANKRUPTCY STATEMENT AGAINST SECURITIES COMPANY - Irfan Ifandi; Muhammad Ashri; Oky Deviany (Surakarta Law and Society Journal, 2019)
This study aims to analyze and explain the legal standing of bankruptcy applicants against securities companies andinvestor protection in stock transactions, as well as the settlement process at securities companies PT. Andalan Artha Advisindo Securitas. This research is a normative research with a legislative approach and conceptual approach. The research data is in the form of primary legal material relating to the object of research. The results of the study indicate that the legal standing of the applicant's statement of bankruptcy against the securities company is confirmed in UUK and PKPU that only OJK has the authority to submit a statement of bankruptcy to the securities company. So, there should be no other institution or individual, except OJK which can submit a statement of bankruptcy against the securities company. In addition, investor protection in share transactions includes: forming a division that specifically deals with education and consumer protection in the financial services sector that is intended for investors or the general public in accordance with the prevailing laws and regulations. Whereas the alternative settlement process for securities companies is in two forms of preventive measures in the form of clear regulatory arrangements, the existence of standard guidelines, guidance and direct direction from OJK.